RNAi-Related Dicer and Argonaute Proteins Play Critical Roles for Meiocyte Formation, Chromosome-Axes Lengths and Crossover Patterning in the Fungus Sordaria macrospora - Girard, Chloe; Budin, Karine; Boisnard, Stéphanie; Zhang, Liangran; Debuchy, Robert; Zickler, Denise; Espagne, Eric (Frontiers in Cell and Developmental Biology, 2021)
RNA interference (RNAi) is a cellular process involving small RNAs that target and regulate complementary RNA transcripts. This phenomenon has well-characterized roles in regulating gene and transposon expression. In addition, Dicer and Argonaute proteins, which are key players of RNAi, also have functions unrelated to gene repression. We show here that in the filamentous Ascomycete Sordaria macrospora, genes encoding the two Dicer (Dcl1 and Dcl2) and the two Argonaute (Sms2 and Qde2) proteins are dispensable for vegetative growth. However, we identified roles for all four proteins in the sexual cycle. Dcl1 and Sms2 are essential for timely and successful ascus/meiocyte formation. During meiosis per se, Dcl1, Dcl2 and Qde2 modulate, more or less severely, chromosome axis length and crossover numbers, patterning and interference. Additionally, Sms2 is necessary both for correct synaptonemal complex formation and loading of the pro-crossover E3 ligase-protein Hei10. Moreover, meiocyte formation, and thus meiotic induction, is completely blocked in the dcl1 dcl2 and dcl1 sms2 null double mutants. These results indicate complex roles of the RNAi machinery during major steps of the meiotic process with newly uncovered roles for chromosomes-axis length modulation and crossover patterning regulation.